ESS Cryogenic System Process Design. Issue 1 (November 2015) - Arnold, P; Hees, W; Jurns, J; Su, X T; Wang, X L; Weisend, J G
Abstract: The European Spallation Source (ESS) is a neutron-scattering facility funded and supported in collaboration with 17 European countries in Lund, Sweden. Cryogenic cooling at ESS is vital particularly for the linear accelerator, the hydrogen target moderators, a test stand for cryomodules, the neutron instruments and their sample environments. The paper will focus on specific process design criteria, design decisions and their motivations for the helium cryoplants and auxiliary equipment. Key issues for all plants and their process concepts are energy efficiency, reliability, smooth turn-down behaviour and flexibility. The accelerator cryoplant (ACCP) and the target moderator cryoplant (TMCP) in particular need to be prepared for a range of refrigeration capacities due to the intrinsic uncertainties regarding heat load definitions. Furthermore the paper addresses questions regarding process arrangement, 2 K cooling methodology, LN2 precooling, helium storage, helium purification and heat recovery.